КРЕДИТНО-МОДУЛЬНА СИСТЕМА ОЦІНЮВАННЯ ЗНАНЬ І УМІНЬ СТУДЕНТІВ З ФІЗИЧНОГО ВИХОВАННЯ (Педагогіка вищої та середньої школи, 2022)
The problems of the European credit-transfer system's introduction into the training process of Ukrainian highev educational establishments in "Physical Training” discipline, the process of the self dépendent work’s organization in physical training are examined in the article.